O impacto das quedas sobre a aptidão funcional-física de mulheres idosas - Vitor, Priscila Regina Rorato (2013)
During the life, individuals can suffer with a falls and its consequences; however, fall can be more aggravating problem in older adults. In the case of a older adults had suffered a fall, it can result to a fracture and, consequently, the treatment of the condition can lead to a temporary or prolonged dependency period, influencing negatively the independent life status. Purpose: to analyze the impact of falls on functional fitness of older women. Methods: Seventy-eight older women participated in this study. Cases of falls and the fear of falling were self-reported by the older women, while the functional fitness was measure with a Functional Tests Battery. Mean and standard deviation were used to describe the sample. Independent T-test was used to compare functional fitness between groups. Results: Prevalence of falls in this sample was of 32.4%. Among women fallers, 40% self-reported an elevated fear of falling. Discussion: Neither of the functional fitness component differed statistically between fallers and nonfallers groups; however, it was observed women fallers showed a lower functional fitness, specifically related to strength, balance and agility capacities. Therefore, interventions need to be developed for improving these capacities with the purpose to prevent falls, as well as the consequences of this process, such as osteoporotic fractures. It is recommended that functional and resistance exercises being included in the preventive strategies for reducing risk factors for falls and its determinants in older women.